What ἐν τῷ κόσμῳ are the στοιχεῖα τοῦ κόσμου? - Dieter T. Roth (HTS Teologiese Studies/Theological Studies, 2014)
The expression τὰ στοιχεῖα τοῦ κόσμου is one of the most discussed, and most disputed, phrases in Galatians. In the following article, insight into the meaning of this phrase is sought by first of all clarifying and summarising the full scope of issues which must be explained by any interpretation of the phrase. Such a summary overview has often not appeared in various scholarly discussions. Subsequently, the primary proposed interpretations are discussed with the argument ultimately being made that it is Paul’s conception of ‘the world’ which provides the key to a solution to the interpretive conundrum that best satisfies the entire context of Paul’s letter and argument.